The effects of orthographies, stress and consonantal manners on syllabification and acoustic durations of intervocalic consonants with singleton and geminate graphemes by Thai L2 speakers of English - Anusorn Saechan,; Sugunya Ruangjaroon, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research investigates how orthographies, stress, and consonantal manners influence syllabification and acoustic durations of intervocalic consonants by Thai L2 English speakers, who were classified into three CEFR English proficiency levels: A1, A2 and B1 and participated in two tasks. The first task aims to examine syllabification, known as a word-part identification task, wherein the participants were instructed to identify the first part of a word in one question item and the second part of the same word in another. The findings reveal dynamic changes in syllabification preferences as L2 proficiency increases. The initial stages of acquisition display a strong reliance on orthographic forms for syllabification. An increase in proficiency is associated with a growing awareness of the interaction of stress with syllabification but a declining reliance on orthography. The second task aims to investigate the production, referred to as a read-aloud task where the participants were asked to read aloud target words in carrier sentences. The durations of intervocalic consonants were analyzed using Praat software (Boersma & Weenink, 2021) based on waveforms and spectrograms. The results indicate that participants at all levels produced intervocalic consonants orthographically represented as geminates significantly longer in duration than those represented as singletons. The durational ratio of orthographic singletons to geminates is overall greater for intervocalic consonants in pre-stress positions than for those in post-stress positions. This ratio steadily decreases from A1 to native English speakers. The findings from both tasks consistently show that higher English proficiency correlates with native-like syllabification and acoustic duration.